Control interno y su incidencia en el proceso administrativo y financiero de la empresa comercial “Distribuidora Mendoza” de la ciudad de El Empalme, año 2014 - Heredia Sánchez, Xiomara (2015)
This research has the design of an internal control departments Empresa Distribuidora Mendoza in the Province of Guayas in the canton El Empalme. They were used as targets, evaluate internal control and administrative and financial impact of the company during 2014, diagnose the present situation of the company under the COSO I report, implement financial and management indicators to measure efficiency, effectiveness and economy of the company issuing the report Internal Control of the company, develop a manual of procedures for optimizing procedures Distribuidora Mendoza. Internal Control of the company was conducted under the COSO I system and its five components: Control Environment, Risk Assessment, Control Activities, Information - Communication, Monitoring and issuing the report, in order to detect each of the weaknesses in the different departments of the company. To achieve the objective methods, inductive which to analyze the company in general is used, the analytical method to analyze the company in each of its departments, to study systemic problems of the company, and inductive reasoning to display and processes in the company Distribuidora Mendoza. Demonstrating weaknesses in their departments, which can be analyzed and corrected by processes and functions set forth in each of their departments.